Early caloric deficit is associated with a higher risk of death in invasive ventilated COVID-19 patients. Issue 12 (December 2022) - Cereda, Emanuele; Guzzardella, Amedeo; Klersy, Catherine; Belliato, Mirko; Pellegrini, Andrea; Sciutti, Fabio; Mongodi, Silvia; Masi, Sara; Crotti, Silvia; Savioli, Monica; Zanella, Alberto; Mojoli, Francesco; et al.
Summary: Background & aims: The aim of this study was to evaluate the nutritional support management in mechanically ventilated coronavirus disease 2019 (COVID-19) patients and explore the association between early caloric deficit and mortality, taking possible confounders (i.e. obesity) into consideration. Methods: This was a prospective study carried out during the first pandemic wave in the intensive care units (ICUs) of two referral University Hospitals in Lombardy, Italy. Two hundred twenty-two consecutive mechanically ventilated COVID-19 patients were evaluated during the ICU stay. In addition to major demographic and clinical data, we recorded information on the route and amount of nutritional support provided on a daily basis. Results: Among patients still in the ICUs and alive on day 4 (N = 198), 129 (65.2%) and 72 (36.4%) reached a satisfactory caloric and protein intake, respectively, mainly by enteral route. In multivariable analysis, a satisfactory caloric intake on day 4 was associated with lower mortality (HR = 0.46 [95%CI, 0.42–0.50], P < 0.001). Mild obesity (body mass index [BMI] ≥30 and < 35 kg/m 2 ) was associated with higher mortality (HR = 1.99 [95%CI, 1.07–3.68], P = 0.029), while patients with moderate-severe obesity (BMI≥35 kg/m 2 ) were less likely to be weaned from invasive mechanical ventilation (HR = 0.71 [95%CI, 0.62–0.82], P < 0.001). Conclusions: This study confirmed the negative prognostic and clinical role of obesity in mechanically ventilated COVID-19 patients and suggested that early caloric deficit may independently contribute to worsen survival in this patients' population. Therefore, any effort should be made to implement an adequate timely nutritional support in all COVID-19 patients during the ICU stay.